Morphological and molecular studies of Eudiplozoon nipponicum (Goto, 1891) and Eudiplozoon kamegaii sp. n. (Monogenea; Diplozoidae) - Nishihira, Tomoki; Urabe, Misako (Folia parasitologica, 2020)
Eudiplozoon nipponicum (Goto, 1891) Khotenovsky, 1985 (Monogenea: Diplozoidae), is known to parasitise Cyprinus carpio Linnaeus and species of Carassius. In this study, we conducted a taxonomic re-examination of E. nipponicum using genetic analysis and morphological comparisons from different host species from a single water system. rDNA nucleotide sequences of the internal transcription spacer 2 (ITS-2) region (645 bp) showed interspecific-level genetic differences among diplozoids from species of Carassius and C. carpio (p-distance: 3.1-4.0%) but no difference among those from different species of Carassius (0-0.4%) or between those from C. carpio collected in Asia and Europe (0-1.1%). Large variation was observed among 346 bp cytochrome c oxidase subunit I (COI) sequences (0.3-16.0 %); the topology of the phylogenetic tree showed no relationship to host genera or geographical regions of origin. Morphological observation showed that average clamp size of diplozoids from C. carpio was larger than those from Carassius spp. The number of folds on the hindbody was 10-25 for diplozoids from C. carpio and 12-19 for those from Carassius spp. Thus, our ITS-2 sequence and morphological comparison results indicate that diplozoids from C. carpio and species of Carassius belong to different species. The scientific name E. nipponicum should be applied to the species infected to the type host, Carassius sp. of Nakabo (2013) (Japanese name ginbuna). The diplozoid infecting C. carpio (Eurasian type) should be established as a new species: Eudiplozoon kamegaii sp. n. A neotype of E. nipponicum is designated in this report because the original E. nipponicum specimens are thought to have been lost.
Keywords: nemoci ryb; neotype; DNA, Ribosomal; Phylogeny; Fish Diseases; kapři; Japonsko; host specificity; Trematoda; morphology; Trematode Infections; infekce červy třídy Trematoda; Lakes; zvířata; Japan; jezera; Carps; fylogeneze; monogenea; ribozomální DNA; new species; genus Eudiplozoon; Animals; molecular phylogeny